The influence of the MOF shell thickness on the catalytic performance of composites made of inorganic (hollow) nanoparticles encapsulated into MOFs. Issue 24 (14th November 2016) - Yazdi, A.; Mercoçi, F.; Bastús, N. G.; Imaz, I.; Puntes, V.; Maspoch, D.
Abstract : A series of ZIF-8 composites containing hollow Pt or Pd nanoparticles show that the size and the MOF shell thickness play a key role in the catalytic performance of this class of composites. Abstract : Herein we report the encapsulation of hollow Pt or Pd nanoparticles into ZIF-8, making a series of composites in which the ZIF-8 shell thickness has been systematically varied. By using these composites as catalysts for the reduction of 4-nitrophenol and Eosin Y, we show that the MOF shell thickness plays a key role in the catalytic performance of this class of composites.